Vaccination and tick-borne encephalitis, central Europe - Heinz, Franz X; Stiasny, Karin; Holzmann, Heidemarie; Grgic-Vitek, Marta; Kříž, Bohumír; Essl, Astrid; Kundi, Michael (Emerging infectious diseases, 2013)
Tick-borne encephalitis (TBE) is a substantial public health problem in many parts of Europe and Asia. To assess the effect of increasing TBE vaccination coverage in Austria, we compared incidence rates over 40 years for highly TBE-endemic countries of central Europe (Czech Republic, Slovenia, and Austria). For all 3 countries we found extensive annual and longer range fluctuations and shifts in distribution of patient ages, suggesting major variations in the complex interplay of factors influencing risk for exposure to TBE virus. The most distinctive effect was found for Austria, where mass vaccination decreased incidence to =16% of that of the prevaccination era. Incidence rates remained high for the nonvaccinated population. The vaccine was effective for persons in all age groups. During 2000-2011 in Austria, =4,000 cases of TBE were prevented by vaccination.
Keywords: Encephalitis Viruses, Tick-Borne; novorozenec; Infant, Newborn; Infant; Humans; Risk; kojenec; lidé středního věku; Encephalitis, Tick-Borne; klíšťová encefalitida; dítě; Child; viry klíšťové encefalitidy; Viral Vaccines; Female; věkové faktory; lidé; Rakousko; mladiství; předškolní dítě; Austria; ženské pohlaví; Slovenia; Male; Middle Aged; Adolescent; incidence; Incidence; Mass Vaccination; Czech Republic; Age Factors; Česká republika; mužské pohlaví; Child, Preschool; hromadná vakcinace